Morphology–Transport Coupling and Dissipative Structures in PEO–PS+LiTFSI Electrolytes In-Operando Conditions - Tagliazucchi, Mario Eugenio (2025)
A Single-Chain-in-Mean-Field (SCMF) algorithm was introduced to study block copolymer electrolytes in nonequilibrium conditions. This method self-consistently combines a particle-based description of the polymer with a generalized diffusion equation for the ionic fluxes, thus exploiting the time scale separation between fast ion motion and the slow polymer relaxation and self-assembly. We apply this computational method to study ion fluxes in electrochemical cells containing poly(ethylene oxide)-polystyrene (PEO–PS) block copolymers with added lithium salt. Blocking of the anion fluxes by the electrodes in-operando conditions polarizes the cells and results in an inhomogeneous salt-concentration profile. This gradient of salt concentration triggers lamellae-to-disorder and disorder-to-lamellae transitions near the electrodes, in good agreement with previous experimental observations. The effects of the selectivity of the electrode surface, the salt concentration and the voltage applied to the cell are systematically studied. For PEO-selective surfaces, the lamellae parallel to the electrode that forms at low applied potentials transition to a bicontinuous morphology at high applied potentials in order to allow ion transport through the insulating PS layers. The formation of this dissipative structure, which is unexpected considering the equilibrium behavior of the material, is in line with the principle of maximum entropy production. In summary, the transport and morphology in PEO–PS electrolytes are strongly coupled: ionic currents influence self-assembly, which in turn modulates the ionic fluxes in the cell.